The Role of Digital Marketing in Increasing Consumer Buying Interest in the Shopee Marketplace - Sulfitri; Adam Latif; Andi Riska Andreani Syafaruddin (International Journal of Sustainable Applied Sciences, 2024)
In recent years, Indonesian people have been fond of shopping online (e-commerce) through marketplaces, one of which is Shopee. Buying interest is a manifestation of consumer attraction to a company's products or services. This study aims to determine the role of digital marketing in consumer buying interest, especially in the Faculty of Economics and Business, University of Muhammadiyah Sidrap. This study uses a quantitative method. Students of the Faculty of Economics and Business, University of Muhammadiyah Sidrap are the population of the study which amounted to 245 people, the total sample used was 15% of the total population or 36 respondents. Data collection uses the questionnaire method. The instrument used was a questionnaire using a Likert scale. Data analysis using SPSS (Statistical Package for the Social Sciences) software , this research will be carried out at the Faculty of Economics and Business